ANALYSIS OF BREAKDOWN OF LOGISTIC COSTS IN A LARGE BRAZILIAN COMPANY - Terazzi, Luis Fernando; Queiroz, Marcelo Fachini; de Camargo Junior, João Batista (Revista Interface Tecnológica, 2020)
In the quest to meet the needs of consumers in a more assertive way and thus gain competitive advantage, companies seek to develop their management processes. In this context, a model called World Class Manufacturing can contribute to the improvement of operations in an organization. One of the main pillars of this model is cost deployment, which helps to identify losses in several areas. Considering the importance of logistics for a company, and also the fact that this area is one of the pillars of the model, the objective of this work is to analyze how the cost deployment of logistics is applied in a large Brazilian company and which main causal losses are identified by this tool. The methodology used to achieve this purpose was qualitative, exploratory research, through a case study in a white line multinational. Interviews were conducted with three managers from three production units of the company, in addition to monitoring operations. The results of the work indicate that cost deployment is applied based on five main variables of logistical costs, and that the main causal losses include inadequate packaging, inadequate line supply, distance from the supplier, plant layout and inventory accuracy.